2019
DOI: 10.1002/jbm.b.34487
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan‐laponite nanocomposite scaffolds for wound dressing application

Abstract: The pivotal issue of skin regeneration research is the development of effective biomaterials that exhibit biological activities as fungicide and bactericide, combining simple and low cost manufacturing technologies. In this context, nanocomposite scaffolds based on chitosan (Ch)/Laponite (Lap) were produced by using different concentrations of Lap via freeze‐drying process for potential application in skin regeneration. The influence of Lap concentration on the scaffold properties was evaluated. The prepared s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…The viability of cells on PCL and PCL@CMC scaffolds was also assessed for the comparison. Results showed that the cell viability was significantly improved from PCL to PCL@CMC and PCL@CMC/LAP3.5% during this time (Figure 3B) Gonzaga et al reported that the addition of LAP nanoplatelets to chitosan enhanced the cell proliferation on the corresponding scaffolds 24 …”
Section: Resultsmentioning
confidence: 84%
“…The viability of cells on PCL and PCL@CMC scaffolds was also assessed for the comparison. Results showed that the cell viability was significantly improved from PCL to PCL@CMC and PCL@CMC/LAP3.5% during this time (Figure 3B) Gonzaga et al reported that the addition of LAP nanoplatelets to chitosan enhanced the cell proliferation on the corresponding scaffolds 24 …”
Section: Resultsmentioning
confidence: 84%
“…The porosity of the bioscaffolds was determined by liquid displacement method [35]. The weight (W 1 ) and volume (V) of bioscaffolds were measured before the immersion into ethanol.…”
Section: Porosity Measurementmentioning
confidence: 99%
“…After the saturation of bioscaffolds by the absorption of ethanol, the weight of bioscaffolds were measured again (W 2 ). The porosity of the bioscaffolds was calculated according to the Equation (2) (ρ represents the density of the ethanol) [35]. All experiments were performed in triplicate.…”
Section: Porosity Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…Laponite ® was also processed with chitosan to develop a scaffold for wound healing applications. The material had an increase in porosity and an improvement in the mechanical properties after the addition of the clay [17]. Laponite ® was added to a gellan gum's injectable hydrogel to confer stability and strength to the obtained material [18].…”
Section: Introductionmentioning
confidence: 99%